2018
DOI: 10.1371/journal.ppat.1007477
|View full text |Cite
|
Sign up to set email alerts
|

CDHR3 extracellular domains EC1-3 mediate rhinovirus C interaction with cells and as recombinant derivatives, are inhibitory to virus infection

Abstract: Viruses in the rhinovirus C species (RV-C) are more likely to cause severe wheezing illnesses and asthma exacerbations in children than related isolates of the RV-A or RV-B. The RV-C capsid is structurally distinct from other rhinoviruses and does not bind ICAM-1 or LDL receptors. The RV-C receptor is instead, human cadherin-related family member 3 (CDHR3), a protein unique to the airway epithelium. A single nucleotide polymorphism (rs6967330, encoding C529Y) in CDHR3 regulates the display density of CDHR3 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 56 publications
(76 reference statements)
2
38
0
Order By: Relevance
“…Contrary to earlier reports, [3][4][5][7][8][9] in which CDHR3 mediated both rhinovirus C binding and infection of cells, Everman et al 6 found that CDHR3 knockdown did not affect binding of rhinovirus C, whereas it affected rhinovirus C replication. The underlying reason for these apparent discordant results is not clear.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Contrary to earlier reports, [3][4][5][7][8][9] in which CDHR3 mediated both rhinovirus C binding and infection of cells, Everman et al 6 found that CDHR3 knockdown did not affect binding of rhinovirus C, whereas it affected rhinovirus C replication. The underlying reason for these apparent discordant results is not clear.…”
mentioning
confidence: 58%
“…Modeling of the CDHR3 structure suggested potential binding sites for the capsid proteins VP1 and VP2 of rhinovirus C. Mapping of the rhinovirus C binding site or sites on CDHR3 revealed that extracellular domain 1 is the likely docking site for all rhinovirus C types, which was also supported by the capacity of extracellular domain 1-containing proteins/peptides to inhibit rhinovirus C infection of susceptible cells. 4 Sequence analysis of a rhinovirus C strain that displayed improved binding and replication in in vitro cultures showed that a mutation in the viral capsid protein VP1 was indeed responsible for the improved binding. 5 Together, these data are highly suggestive of CDHR3 being the docking site for rhinovirus C types, but independent confirmation is still required.…”
mentioning
confidence: 99%
“…The archetype adhesion function of classic cadherins is achieved by homotypic or heterotypic EC1 strand-swapping requiring one or two N-proximal tryptophan residue(s) (33,34). EC1 and EC1+2 recombinant proteins are monomers in solution (24), and there is no homologous N-proximal tryptophan, so CDHR3 must necessarily use an alternative strategy for adhesive binding (35). The new structure shows that the upper face of EC1 away from the virus has a deep groove-like feature between strands D and C ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Each repeat sequence is consistent with a cadherin seven-strand β-sandwich fold. The native protein has three mapped N-linked glycosylation sites (N186, N384, and N624) which become further sialylated when the Y529 variant is expressed in tissue culture (24). This particular residue, at the junction of the EC5 and EC6 repeats, presumably helps regulate structurally stabilizing interdomain Ca 2+ binding, without which cadherins are improperly trafficked and/or withdrawn from cell surfaces (25)(26)(27).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation